Faktor-Faktor Pemanfaatan Koleksi Perpustakaan di MTSN Sungai Geringging Kabupaten Padang Pariaman - Adestama, Rian; Nelisa, Malta (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2018)
AbstractThe goal of this research is to know the internal and external factors in utilizing library collections in the Geringging River MTsN. This type of research are descriptive, research was carried out in October 2018. Research population numbering 226 students. Sample research amounted to 45 students. Sampling techniques using Purposive Sampling. Insturmen research with deployment now. Data were analyzed with the frequency distribution formula in the form of a percentage. Research results through two factors i.e. internal factors (needs, motives and interests) and external factors (the completeness of the collection, pustakawanan skills in serving the users, the availability of on-site appointment back information). From the spread of the now disimpulan that the internal factor of utilization of library collection in Geringging River MTsN Padang Pariaman are in the category of medium with a percentage (51.27%). External factors and the utilization of library collection in Geringging River MTsN Padang Pariaman are in both categories with percentages (62.91%).Keywords: internal factors and external factors of library collections